Mitigating Leakage Current Suppression with Improved Power Quality Using Four Leg Inverters - Suresh, K.; Vignesh, Mano; Allam, Thirupathi; Lakshmi, D.; S., KavinK; Karthikeyan, D. (2024 International Conference on Advancement in Renewable Energy and Intelligent Systems (AREIS), 2024)
This paper presents a novel approach to mitigating leakage current suppression and improving power quality using four-leg inverters. Leakage currents in electrical systems, particularly in renewable energy applications and grid-connected inverters, can cause significant safety and performance issues, such as corrosion and power loss. The proposed method utilizes a four-leg inverter, which includes an additional leg compared to traditional three-phase inverters, enabling better control of unbalanced and distorted loads. This configuration helps suppress leakage currents by providing enhanced control over neutral point voltage, thus improving overall system stability and power quality. The four-leg inverter also offers improved harmonic compensation, reduces voltage fluctuations, and enhances the system's ability to handle nonlinear and asymmetrical loads, leading to a more reliable and efficient power delivery. Simulation results demonstrate that the four-leg inverter significantly reduces leakage current while maintaining high power quality, making it an effective solution for modern power systems and renewable energy integration. In order to verify the proposed controls, a sequence of numerical simulations utilizing the MATLAB 2021a/ Simulink program. The Relift Luo converter has an efficiency of 93.5% and a Total Harmonic Distortion (THD) Value of Particle Swarm Optimization-Proportional Integral (PSO-PI) Controller is 1.24%, respectively.